2020
DOI: 10.1038/s41598-020-70423-1
|View full text |Cite
|
Sign up to set email alerts
|

Cleavage of human tau at Asp421 inhibits hyperphosphorylated tau induced pathology in a Drosophila model

Abstract: Hyperphosphorylated and truncated tau variants are enriched in neuropathological aggregates in diseases known as tauopathies. However, whether the interaction of these posttranslational modifications affects tau toxicity as a whole remains unresolved. By expressing human tau with disease-related Ser/Thr residues to simulate hyperphosphorylation, we show that despite severe neurodegeneration in full-length tau, with the truncation at Asp421, the toxicity is ameliorated. Cytological and biochemical analyses reve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 72 publications
0
6
0
Order By: Relevance
“…These results are consistent with the absence of Tau aggregation or cell death in cell lines and drosophila expressing TauΔD421 (refs. [45][46][47][48] ). Mice expressing endogenous Tau non-cleavable at D421 unexpectedly show Tau hyperphosphorylation, memory impairment, and synaptic plasticity deficits, indicating that TauΔD421 could be beneficial in this model or that the D421N mutation altered Tau function 32 .…”
Section: Discussionmentioning
confidence: 99%
“…These results are consistent with the absence of Tau aggregation or cell death in cell lines and drosophila expressing TauΔD421 (refs. [45][46][47][48] ). Mice expressing endogenous Tau non-cleavable at D421 unexpectedly show Tau hyperphosphorylation, memory impairment, and synaptic plasticity deficits, indicating that TauΔD421 could be beneficial in this model or that the D421N mutation altered Tau function 32 .…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, based on the previous researches (Chi et al 2020;Han et al 2024Han et al , 2021a, we designed behavioral measurement and analysis methods to quantify indices of locomotion. We rst recorded the activity of virgin male and female ies in test tubes over a day using our custom-developed system and employed a Python 3.5 script to capture the position of fruit ies in every frame of the video.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, a study demonstrated that in mice, blocking Tau cleavage by caspase-3 resulted in memory deficits ( Biundo et al, 2017 ). In Drosophila , caspase 3 cleavage of hyperphosphorylated Tau prevented its toxicity and allowed recovery of motor deficits ( Chi et al, 2020 ). From these results, it appears that the increased cleavage of Tau by caspase-3 upon VAMP8 overexpression could be neuroprotective.…”
Section: Discussionmentioning
confidence: 99%